HALAL CRITICAL POINT ANALYSIS OF SOME TOAST SAMPLES IN CIBIRU DISTRICT, BANDUNG CITY - Mumtazah, Muna; Wardatul Jannah, Annisa; Mauludiyyah Inayatulloh, Hilma; Supriyatna, Ateng (Indonesia Journal of Halal, 2023)
Abstract : The halalness of a food product is still a hot topic in public discussion. The halal quality of food and beverage products does not always depend on the raw materials used. However, it can be known from the mixing materials used, starting from the production process to the distribution process. Muslims are required to eat food that is halal and thoyyib, the critical point of an important product. The critical point of halal is a stage of food production where there is a possibility for a product to become haram. The purpose of this study is to determine the critical point of halal toast products in the Cibiru area, Bandung City. The method used is direct field research by way of observation, interviews, and documentation related to the required data. Furthermore, data analysis was carried out and described in accordance with data collection when in the field. So that the results show that there are critical points in the composition of toast, namely plain bread, jam, and margarine as well as critical points in the tools used, namely baking sheets and brushes.